2006
DOI: 10.5005/jcdp-7-5-26
|View full text |Cite
|
Sign up to set email alerts
|

Microleakage of Seven Adhesive Systems in Enamel and Dentin

Abstract: Aim:The aim of this study was to evaluate the microleakage of seven adhesive systems on two substrates (enamel and dentin). Methods and Materials:Class V cavities were performed in buccal and lingual surfaces of 56 bovine incisors. The cervical margin was located in dentin and the incisal margin in enamel. The specimens were randomly divided into seven groups (n=16), according to the adhesive system employed: Single Bond; Excite; One Step Plus; Gluma One Bond; Magic Bond; One Up Bond F; and One Coat Bond. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The high score from the two sections of each specimen was then recorded, representing the total amount of microleakage over the entire specimen to simplify the findings. Araujo CS, et al [ 29 ] recommended criteria were used to record microleakage as shown in (Table 1 ) Fig. 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The high score from the two sections of each specimen was then recorded, representing the total amount of microleakage over the entire specimen to simplify the findings. Araujo CS, et al [ 29 ] recommended criteria were used to record microleakage as shown in (Table 1 ) Fig. 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Then all teeth were stored in distilled water at 37ºc for one month. After this the teeth were thermocycled 500 time at a temperature of 5ºc±2ºc and 55ºc±2ºc, with dwell times of 60 second in each water bath and 60 second transfer time between the baths (1) .For all specimens the entire tooth surface were painted with two coats of nail varnish except for an area of 1mm a way from the cavosurface margins to prevent dye penetration anywhere other than the restoration margins.The samples were immersed in 2% methylene blue solution at 37ºc for 24hs (10) . Then the teeth were rinsed in running water, dried and then sectioned buccolingually at the center of the cavity using a diamond wheel saw (KG Sorensen SP, Brazil).…”
Section: Methodsmentioning
confidence: 99%
“…Nanocomposites are the premises of new materials that can be applied in many fields due to their improved mechanical properties (determined by the reinforcement of nanoparticles in the organic part), to their lightweight, and to their light conducting properties. (1)(2)(3)(4)(5) .It is important for the longevity of resin composite restorations that the formation of marginal gaps and cracks can be prevented or at least controlled to the greatest degree possible, if this could be achieved, it would be possible to minimize microleakage and its consequences, such as post operative sensitivity, pulp inflammation and caries recurrence, which are known to jeopardize the clinical longevity of the restoration (1,2) .Dentinal surface morphology and smear layer formation are the main factors in the successful union of dental structure and restoration (3)(4)(5)(6)(7)(8) .There has always been a keen interest in the adaptation of dental restorative materials to the wall of the cavity and the retentive ability of a material to seal the cavity against ingress of oral fluids and microorganisms (9) .New adhesive systems continually have been improved to obtain an effective sealing at tooth/restoration interfaces.Polymerization contraction stress is still one of the major problems when restoring teeth with resin composite since a contraction forces can be created and may disrupt the bond to cavity walls or create stresses to surrounding tooth structure and may result of tooth cracks or fractures. The Polymerization shrinkage and the viscosity were found to be a significant determinants of gap formation around resin composite (1,10,11) .Microleakage is defined as the clinically detectable passage of bacteria, fluids, molecules or ions between a cavity wall and the restorative materials applied to it and is the major problem in clinical dentistry.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the adhesive failure of brackets remains a limitation during treatment. Therefore, various surface treatments such as sandblasting (Arici et al, 2006 ; MacColl et al, 1998 ; Ozer & Arici, 2005 ), silicoating (Newman et al, 1995 ) and self‐etching primer (Elekdag‐Turk et al, 2008 ) of the metal bracket surface have been developed, which seem to be effective in enhancing bond strength at the bracket‐adhesive interface.…”
Section: Introductionmentioning
confidence: 99%